Spiritual Care pada Orang Dengan HIV/AIDS (ODHA) untuk Mencegah Persepsi Citra Diri Negatif - Tia Setiani; Eneng Linda Andriyan; Dewi Fitriani; Rahmania Abdan; Fany Syarifah Mudaim; Intan Niki Widyanisya; Iqmal Noor Alwadhy (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Prevent the perception of negative self-image in people lived with HIV/AIDS (PLWHA) and increase positive self-image. The method used is by providing education through the Telenursing method. The final result achieved in this community service is to prevent the perception of negative self-image in PLWHA. Objective: Implementation of spiritual care for PLWHA to prevent the perception of negative self-image. Method: This community service uses an educational method that is carried out by telenursing. Researchers used observation sheets as a pre-implementation evaluation in the form of a scale of knowledge, perceptions, beliefs, moral views, beliefs, and attitudes. Telenursing is the use of technology as a method of providing long-distance health services so that patients and nurses do not need to meet face-to-face. This community service research is divided into 4 stages. Namely Environmental surveys and targets, Preparation of facilities and infrastructure, Implementation of community service education, and Evaluation. This activity was attended by 10 respondents under the auspices of the association of HIV/AIDS prevention activities in Ciamis Regency. Result: The results of spiritual care for PLWHA to prevent the perception of negative self-image as a form of implementing community service for 10 PLHAs in the Ciamis district show that it does not provide significant results because there are other inhibiting factors such as support and negative community stigma in the community. people living with HIV. Conclussion: Spiritual care has a positive impact on various parties, especially people with HIV/AIDS. Improved self-image is not only created from internal factors but must also be supported by various parties. Community service activities held regarding spiritual care for people with HIV/AIDS to prevent the perception of a negative self-image received a good response from PLWHA.